O04 Fetal Outcome following Dydrogesterone Exposure in Pregnancy. Issue 6 (17th May 2019) - Koren, G; Gilboa, D; Rotem, R; Levy, A; Daniel, S; Shalev, V
Abstract : Background: The progestin dydrogesterone (DYD) is widely used for threatened and recurrent miscarriages, as well as for dysfunctional bleeding, infertility and other obstetric and gynecological indications. While its apparent efficacy has been compared to other progestins, its fetal safety has not been investigated. Objectives: To follow up fetal outcome after gestational exposure to DYD. Patients and methods: Using a 2.5 million patients´ database, we compared congenital malformations among babies exposed in utero to DYD between 1999 and 2016, to a control group not receiving this medication. We adjusted for concomitant exposure to in vitro fertilization (IVF) and to other forms of assisted reproductive technology (ART). Results: There were 8508 children exposed in uteo to DYD (4417 males, 4091 females) out of 777, 422 live births. After excluding cases with concomitant exposure to IVF and other forms of ART, DYD was associated with increased risk for hypospadias [OR 1.28(95% confidence interval 1.06–1.55)], overall cardiovascular malformations [OR 1.18 (1.06–1.33)], spina bifida [OR 2.29(1.32–3.97] and hydrpcephalus [OR 2.04(1.28–3.25]. In additional analysis, including also those exposed to IVF and other forms of ART, there was also increased risk for cryptorchidism [1.37(1.19–1.58)] and congenital dislocation of the hip [OR 1.58(1.42–1.78)]. Conclusions: DYD confers teratogenic effects after exposure to the recommended doses in pregnant women. Some of these adverse fetal effects are further augmented by concomitant use of IVF and other forms of ART. These independent teratogenic effects may have important implication for the child and family. Disclosure(s): Nothing to disclose